Perancangan Desain Pesawat Aeromodelling Model Trainer untuk Pembelajaran Pengendalian Pesawat Berbasis Sistem Komputer: Indonesia - Caniago, Deosa Putra (Computer Science and Information Technology, 2024)
This study aims to design and develop a computer-based trainer model aeroplane for flight control education. The selection of appropriate materials is a primary focus, with polyfoam chosen as the main material for the aircraft body due to its lightweight nature, excellent impact absorption, and resistance to deformation. The research also integrates sensor technology and an automatic control system, enabling real-time flight monitoring. The methodology includes mechanical design, electronic schematics, control system design, and flight performance testing. The results indicate that the aircraft achieves a stability level of 95% and operates effectively under various flight scenarios. This research is expected to make a significant contribution to the development of aviation education technology and provide a more interactive and safe training platform for novice students in the field of aeronautics.